(untitled) (Journal of the College of Basic Education, 2022)
The reforms, including the Urban in the Ottoman Empire of the most important achievements by some Ottoman sultans, but such a strategic project (Railway Damascus - Medina) carried out by the Sultan Abdul Hamid II, was a landmark in its significance the political and economic leaving fingerprints in the psyche Sultan Abdul Hamid and who stood with him in the completion of a project like this, some of the some of the colonial powers, including Britain, which was hindering and foil these projects so it was optional for this study because they carry a lot of goals and meanings charity to link sons one state to each other, especially the political goals and economic, and it was such a real dream projects have been accomplished during the reign of Sultan Abdul Hamid